(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
All innovative products need to have the potential for protection under one or more intellectual property regimes. The intangible intellectual property rights (IPR) give exclusive rights to the creator for their creation. These rights boost innovative thinking and research, which provide recognition and economic benefits to the creator. However, the lack of knowledge about IPR is the main hitch with developing countries like India. Lacking off IPR knowledge, foreigners steal our resources and ideas and give provision for biopiracy. This article provides the basic information about various types of IPRs viz., patents, trademarks, and geographical indications, industrial designs, copyrights, trade secrets, layout designs, protection of new plant varieties, etc., with basic information about the need and method of getting the same. Each of which consists of a distinct set of rights. Intellectual property regimes, including the vast majority of academic creativity, will result in the subject matter immediately protected under the Copyright Act 1968 as a literary, dramatic, musical, or artistic work in one of the arts. Books, chapters in books, plays, departmental working and discussion papers, journal articles, surveys, reports, conference publications, teaching materials, computer software, multimedia, databases, paintings, photographs, drawings, musical compositions, and arrangements are examples of creative works. Material such as sound recordings (including CDs, tapes, or cassettes), cinematograph films (including videos), television and good broadcasts, and published editions of works are all automatically protected under a separate set of provisions. Performers Need some protection, and Intellectual creativity may result in patentable inventions as well as confidential information. A registered patent can be issued if a new and inventive product or process is developed with commercial utility. These can be anything from a new drug to a computer program to an industrial revolution to new comprehensive educators believe that students need to develop a fundamental understanding of their rights as creators as early as possible in their educational careers. When it comes to using someone else’s creation, technology, and patent consulting firms argue that it is essential to cultivate a culture that respects the creator’s rights and gives proper credit. The purpose of this article is to shed light on the relevance, necessity, utility, and prospects of the utility of intellectual property and in the sphere of legal instruction.